Effect of the Silica-Magnetite Nanocomposite Coating Functionalization on the Doxorubicin Sorption/Desorption - Alexander M. Demin; Alexander V. Vakhrushev; Marina S. Valova; Marina A. Korolyova; Mikhail A. Uimin; Artem S. Minin; Varvara A. Pozdina; Iliya V. Byzov; Andrey A. Tumashov; Konstantin A. Chistyakov; Galina L. Levit; Victor P. Krasnov; et al. (MDPI AG, 2022)
A series of new composite materials based on Fe3O4 magnetic nanoparticles coated with SiO2 (or aminated SiO2) were synthesized. It has been shown that the use of N-(phosphonomethyl)iminodiacetic acid (PMIDA) to stabilize nanoparticles before silanization ensures the increased content of a SiO2 phase in the Fe3O4@SiO2 nanocomposites (NCs) in comparison with materials obtained under similar conditions, but without PMIDA. It has been demonstrated for the first time that the presence of PMIDA on the surface of NCs increases the level of Dox loading due to specific binding, while surface modification with 3-aminopropylsilane, on the contrary, significantly reduces the sorption capacity of materials. These regularities were in accordance with the results of quantum chemical calculations. It has been shown that the energies of Dox binding to the functional groups of NCs are in good agreement with the experimental data on the Dox sorption on these NCs. The mechanisms of Dox binding to the surface of NCs were proposed: simultaneous coordination of Dox on the PMIDA molecule and silanol groups at the NC surface leads to a synergistic effect in Dox binding. The synthesized NCs exhibited pH-dependent Dox release, as well as dose-dependent cytotoxicity in in vitro experiments. The cytotoxic effects of the studied materials correspond to their calculated IC50 values. NCs with a SiO2 shell obtained using PMIDA exhibited the highest effect. At the same time, the presence of PMIDA in NCs makes it possible to increase the Dox loading, as well as to reduce its desorption rate, which may be useful in the design of drug delivery vehicles with a prolonged action. We believe that the data obtained can be further used to develop stimuli-responsive materials for targeted cancer chemotherapy.